Efforts to Grow Democratic Attitudes in Students in the Era of Globalization Through Citizenship Education - Abdal Rizky Munthe; Fadiah Adlina; Khairunnisa; Lutfi Aulia (Journal of Contemporary Gender and Child Studies, 2022)
The implementation of civic education in higher education is a must in the national education system to prepare smart and responsible citizens, and foster a democratic attitude. This paper aims to describe efforts to foster democratic attitudes to citizens, especially students through Citizenship Education. This research uses a qualitative approach with a literature study method. The results of this study indicate that: (1) civics education is one way to form a complete Indonesian human being as an embodiment of the individuality of the nation as a democratic country that can realize and implement the development of a democratic society. (2) Efforts to foster democratic attitudes and the spirit of nationalism are not only the responsibility of the government as state administrators, but also require the active role of the community, especially the role of the family.